If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying g(y + 6) = 0 Reorder the terms: g(6 + y) = 0 (6 * g + y * g) = 0 (6g + gy) = 0 Solving 6g + gy = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'g'. g(6 + y) = 0Subproblem 1
Set the factor 'g' equal to zero and attempt to solve: Simplifying g = 0 Solving g = 0 Move all terms containing g to the left, all other terms to the right. Simplifying g = 0Subproblem 2
Set the factor '(6 + y)' equal to zero and attempt to solve: Simplifying 6 + y = 0 Solving 6 + y = 0 Move all terms containing g to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + y = 0 + -6 Combine like terms: 6 + -6 = 0 0 + y = 0 + -6 y = 0 + -6 Combine like terms: 0 + -6 = -6 y = -6 Add '-1y' to each side of the equation. y + -1y = -6 + -1y Combine like terms: y + -1y = 0 0 = -6 + -1y Simplifying 0 = -6 + -1y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
g = {0}
| (3x-1)/4-2x+1/5=(7x-13)/20 | | 32+5=2x+13 | | 0=1.5x^2-8x+8 | | 2x+4x+3y-y= | | -3m+1=9-15 | | 104=2(x+16)+x | | r=1/3d(60-t) | | -5x-4=16+x | | 2x+40=4x+22 | | D(t)=4.9t^2-0.1t^3 | | 8x+204=6x+180 | | |2-5|= | | 3(2n+4)=30 | | 6x-16=104 | | 7-9z=81+z | | 4x^2-19x+17=-6x+7 | | 4r+(7*4)=72 | | 3a-5=18 | | F(x)=4x-3x^2-x^3 | | D(t)=4.9t^2 | | 2-(3x-20)=11-10x | | =x(24-2x)(45-2x) | | x^2+y^2-7x-7y+12=0 | | 3x-2/8=40 | | 15x-15x=12 | | 2(3t-4)=10t-7 | | 6-7x=5x-9x+6 | | 9x-27=8x-7 | | 4n^2+4n-35=0 | | 4y+1Y= | | 3x-45=8x | | 2x-30=-x |